2015
DOI: 10.1371/journal.pone.0132709
|View full text |Cite|
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of ZnO Containing Glasses

Abstract: A new family of non-toxic biocides based on low melting point (1250°C) transparent glasses with high content of ZnO (15–40wt%) belonging to the miscibility region of the B2O3-SiO2-Na2O-ZnO system has been developed. These glasses have shown an excellent biocide activity (logarithmic reduction >3) against Gram- (E. coli), Gram+ (S. aureus) and yeast (C. krusei); they are chemically stable in different media (distilled water, sea-like water, LB and DMEN media) as well as biocompatible. The cytotoxicity was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 48 publications
3
53
1
Order By: Relevance
“…The average particle size of the obtained powder was found to be d 50 = 6.3 ± 0.1 µm. The glass formulation was designed in the miscibility area according to the equilibrium diagram studied by Taylor et al [24] and was chosen based on the high antimicrobial activity shown in a previous study [23]. Al 2 O 3 was added as a stabilizer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average particle size of the obtained powder was found to be d 50 = 6.3 ± 0.1 µm. The glass formulation was designed in the miscibility area according to the equilibrium diagram studied by Taylor et al [24] and was chosen based on the high antimicrobial activity shown in a previous study [23]. Al 2 O 3 was added as a stabilizer.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the complexity as well as the incompletely understood dissolution process of ZnO particulate and coating systems in the mentioned media in this investigation, instead of a zinc oxide system we selected a high ZnO content glass (35 wt %) which has been recently developed by the authors [23]. This glass can be considered chemically stable, non-toxic, and with an excellent activity (>3 log 10 reduction in colony forming-units) against E. coli (Gram-negative), S. aureus (Gram-positive), and C. krusei (yeast).…”
Section: Introductionmentioning
confidence: 99%
“…Another possible mechanism for ZnO antibacterial activity is the release of high zinc ion concentrations, which can damage cell membrane and interact with intracellular contents [19]. In a previous work [18], Zn 2+ released from glasses powder (<30 mm) was found to be ~400 ppm. In the case of the coatings, Zn 2+ release must be significantly lower due to their lower specific surface area in comparison with glass powder.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO containing glasses were previously studied as bactericide powders [18]. It is well reported that ZnO even in the form of nanoparticles exhibits a minimal effect on human and animal cells [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanoparticles are also incorporated in transparent glasses and its antibacterial and antifungal properties were evaluated. These glasses have shown to be functional biocides against E.coli, yeast and S.aureus 15 . These glasses can be used in several applications in textiles, protective hospital apparels, surgical instruments, medical implants, water purification systems, food packs, and storage containers.…”
Section: Introductionmentioning
confidence: 99%